Investigation on Geometrical Complexity Techniques for Assessing AM Feasibility. Issue 1 (16th April 2021) - Greco, Alessandro; Piccicacchi, Giovanni; Manco, Pasquale; Defranchi, Rocco; Ambrico, Michele; Caputo, Francesco; Gerbino, Salvatore
Abstract: Currently, there is a growing interest of industries in applying additive manufacturing (AM) technology for generating objects with high geometrical complexity and low weight, ensuring good performance, comparable to those ones of products realized by means of traditional techniques. Anyway, it is still usual to realize AM products without focusing on the morphology of the object, hence without exploiting all the advantages of the technique. Indeed, since the several suitable AM technologies, it should be useful to know the functional characteristics of the component for the best choice of the appropriate one and its constructive complexity. In this regard, the 3D modeling strategy is extremely crucial for a proper realization of AM products. The paper deals with a study of the geometrical complexity of dashboard components of a car, based on several techniques for evaluating the geometric complexity. The latter is a fundamental element for estimating the feasibility of AM in terms of production costs and the benefits with respect to traditional molding. In detail, the study focuses on comparing several geometrical complexity evaluation techniques in order to identify the one that simplifies the calculation and better approximates the most used in literature.